2008
DOI: 10.1089/tea.2007.0167
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Bone Regeneration by CCN2 Incorporated into Gelatin Hydrogel

Abstract: CCN family protein 2/connective tissue growth factor (CCN2/CTGF) is a unique molecule that promotes the entire endochondral ossification process and regeneration of damaged articular cartilage. Also, CCN2 has been shown to enhance the adhesion and migration of bone marrow stromal cells as well as the growth and differentiation of osteoblasts; hence, its utility in bone regeneration has been suggested. Here, we evaluated the effect of CCN2 on the regeneration of an intractable bone defect in a rat model. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Authors: The microvibration regimen was determined based on existing literatures and our preliminary studies. The optimal parameters of vibration in our study are different from those in vitro and in vivo studies (Rubin et al, 2002;Rubin et al, 2004;Garman et al, 2007;Lau et al, 2010;Patel et al, 2009, text references;Rubin et al, 2001;Maddalozzo et al;2008, de Oliveira et al, 2010. The disparity may due to the various factors, including different devices to produce vibration, different culturing environment and cell types for in vitro study, different subjects for in vivo study, and different conditions between in vivo and in vitro study.…”
Section: Wwwecmjournalorg Y Zhou Et Al Osteogenic Differentiation mentioning
confidence: 61%
See 1 more Smart Citation
“…Authors: The microvibration regimen was determined based on existing literatures and our preliminary studies. The optimal parameters of vibration in our study are different from those in vitro and in vivo studies (Rubin et al, 2002;Rubin et al, 2004;Garman et al, 2007;Lau et al, 2010;Patel et al, 2009, text references;Rubin et al, 2001;Maddalozzo et al;2008, de Oliveira et al, 2010. The disparity may due to the various factors, including different devices to produce vibration, different culturing environment and cell types for in vitro study, different subjects for in vivo study, and different conditions between in vivo and in vitro study.…”
Section: Wwwecmjournalorg Y Zhou Et Al Osteogenic Differentiation mentioning
confidence: 61%
“…Authors: It has been recently been shown by many in vivo studies that LMHF vibration and other kinds of mechanical stimuli exhibit favourable infl uence on bone homeostasis (Rubin et al, 2002;Rubin et al, 2004;Ward et al, 2004;Garman et al, 2007;Rubin et al, 2007, text references;Rubin et al, 2001;Maddalozzo et al, 2008;de Oliveira et al, 2010, additional references). Although the anabolic role of LMHF vibration on bone is achieved by different magnitudes and frequencies of vibration produced with different devices, the time for vibration imposed on these objects is temporal and intermittent.…”
Section: Discussion With Reviewersmentioning
confidence: 99%
“…One of the classical family members, CCN2, is known to be a key factor that promotes harmonized development and regeneration of mesenchymal tissues (Kikuchi et al 2008;Ono et al 2008;Kubota and Takigawa 2011). Nevertheless, the distinct profibrotic function of this same molecule has been widely recognized as well, which function is firmly supported by scientific evidence presented by a number of investigators.…”
Section: Introductionmentioning
confidence: 97%
“…4). Of note, CCN2 in the gelatin hydrogel enables gradual release of CCN2 in vivo up to 14 days (Kikuchi et al 2008).…”
Section: Discussionmentioning
confidence: 99%